Penerapan Self Assessment (Penilaian Diri) Pada Topik Sistem Koordinat Terhadap Hasil Belajar Siswa Kelas VIII - Nurwati Djam’an; Ja’faruddin; Nadzra (Issues in Mathematics Education (IMED), 2017)
This study aims to determine student learning outcomes based on self assessment and assessment conducted by the teacher, knowing the difference in the value of self assessment and assessment carried out by the teacher, and knowing the difference in the average score of the test before and after the implementation of the self assessment. Measurement of student learning outcomes was carried out on the class VIII learning group of SMP Negeri in Makassar. Samples were taken by random sampling technique. Data retrieval method using the instrument used in this study is a self assessment sheet and learning outcomes test. The value of student learning outcomes based on self assessment obtained an average value of 84.60 and the value of student learning outcomes based on assessment conducted by the teacher obtained an average value of 80.83. The difference in the value of self assessment and assessment conducted by the teacher was measured through inferential statistical analysis using SPSS 20.0 and the results of the sig. (2-tailed) 0,000 <α = 0.05 which means that H0 is rejected and H1 is accepted so that the hypothesis is accepted. The difference in the average test scores before and after the application of self-assessment was also measured through inferential statistical analysis using SPSS 20.0 and the results of the sig. (2-tailed) 0,000 <α = 0.05, which means that H0 is rejected and H1 is accepted, which means the hypothesis is accepted. Based on the results of the study it can be concluded that there are differences in the value of self assessment and assessment conducted by the teacher and there are differences in the average scores of tests before and after the application of self assessment.